The Valuation Effects of Geographic Diversification : Evidence From U.S. Banks - Laeven, Luc (IMF Working Papers; Working Paper ;, 2012)
This paper assesses the impact of the geographic diversification of bank holding company (BHC) assets across the United States on their market valuations. Using two novel identification strategies based on the dynamic process of interstate bank deregulation, we find that exogenous increases in geographic diversity reduce BHC valuations. These findings are consistent with the view that geographic diversity makes it more difficult for shareholders and creditors to monitor firm executives, allowing corporate insiders to extract larger private benefits from firms.